ASSESSMENT OF EXTRACELLULAR AND INTRACELLULAR PROTEOLYSIS IN PRETUMOR AND TUMOR DISEASES OF THE LARYNX - I. V. Kondakova; G. V. Kakurina; L. V. Spirina; О. V. Cheremisina; О. V. Pankova; К. Yu. Menshikov (Сибирский онкологический журнал, 2016)
The expression of matrix metalloproteinase (MMP) genes and activity of proteasomes and calpains were studied in patients with precancerous laryngeal lesions and laryngeal cancer. A significant increase in MMP-1 and MMp-14 gene expression was shown in laryngeal cancer tissue compared to that observed in dysplastic laryngeal tissue. Furthermore, the activity of proteasomes and calpains was significantly higher in laryngeal cancer tissue than in dysplastic laryngeal tissue. The results obtained indicate that extracellular and intracellular proteases play an important role in the development of laryngeal cancer. The detected features of pathogenesis of laryngeal dysplasia and laryngeal cancer will allow the additional objective criteria for predicting the risk for malignancy to be identified.